Synthesis of aryl-substituted thieno[3,2-b]thiophene derivatives and their use for N,S-heterotetracene construction - Nadezhda S. Demina; Nikita A. Kazin; Nikolay A. Rasputin; Roman A. Irgashev; Gennady L. Rusinov (Beilstein Journal of Organic Chemistry, 2019)
Fiesselmann thiophene synthesis was applied for the convenient construction of thieno[3,2-b]thiophene derivatives. Thus, new 5- or 6-aryl-3-hydroxythieno[3,2-b]thiophene-2-carboxylates were obtained by condensation of 5- or 4-aryl-3-chlorothiophene-2-carboxylates, respectively, with methyl thioglycolate in the presence of potassium tert-butoxide. The saponification of the resulting esters, with decarboxylation of the intermediating acids, gave the corresponding thieno[3,2-b]thiophen-3(2H)-ones. The latter ketones were used to synthesize new N,S-heterotetracenes, namely 9H-thieno[2',3':4,5]thieno[3,2-b]indoles by their treatment with arylhydrazines in accordance with the Fischer indolization reaction.